NLCs-based solid perfume with pandan (Pandanus amaryllifolius Roxb.) and lemon (Citrus limon Burm.) essential oils - Vanessa Florentia Sanjaya; Liza Pratiwi; Nera Umilia Purwanti (Universitas Ahmad Dahlan, 2026)
Traditional liquid perfumes exhibit significant limitations, including rapid volatilization and limited skin retention (2-4 hours), necessitating advanced delivery systems to enhance fragrance longevity. This investigation developed and optimized solid perfume formulations incorporating nanostructured lipid carriers (NLCs) encapsulating essential oils of pandan (Pandanus amaryllifolius Roxb.) and lemon (Citrus limon Burm.) (EOPL) to achieve prolonged fragrance release and improved stability. Essential oils were isolated via steam distillation methodology, yielding 7.3% (w/w) from pandan leaves and 24.46% (w/w) from lemon peel. NLCs formulation optimization employed three-component simplex lattice design using Design-Expert software version 13.0, with systematic variation of beeswax (solid lipid, 1-10% w/w), EOPL (4-10% w/w), and almond oil (liquid lipid, 4-10% w/w). Twelve experimental runs were comprehensively characterized for pH, percent transmittance at 650 nm, organoleptic properties, homogeneity, and particle-size distribution using dynamic light scattering. Multivariate statistical analysis identified the optimal formulation composition as beeswax:EOPL:almond oil (4:4:10), achieving a desirability function value of 0.909. The optimized NLCs exhibited a physiologically compatible pH (5.884), excellent colloidal stability (99.944% transmittance), nanoscale dimensions (15.37 ± 0.17 nm), and a monodisperse size distribution (PDI = 0.38 ± 0.06). Solid perfume incorporating 10% (w/w) NLCs-EOPL in cera alba matrix (40% w/w) exhibited desirable organoleptic characteristics, thermal stability through six freeze-thaw cycles, and complete dermal safety (Primary Irritation Index = 0.0) in clinical evaluation of 15 volunteers. Consumer acceptability assessment revealed 53.33% purchasing intent, confirming the market viability of this novel NLC-based fragrance delivery platform utilizing indigenous Indonesian botanical resources.